An Overview of International Literature on School Interventions to Promote Mental Health and Well-being in Children and Adolescents - Carta, Mauro Giovanni (Clin Pract Epidemiol Ment Health, 2015)
Introduction: Mental disorders are the largest cause of the burden of disease in the world. Most of the burden affecting adult life has its onset during childhood and adolescence. The European Pact for Mental Health and Wellbeing calls for immediate action and investments in the mental health of children and adolescents. Schools may be the ideal location for promoting health and delivering healthcare services, since schools are a location where young people usually spend their daytime and socialize, schools are easily accessible to families, can provide non-stigmatizing health actions, and form links with the community. Aims and Goals of this Special Issue: This issue is developed within the framework of the Joint Action on Mental Health promoted by the European Commission. This special issue presents a set of systematic reviews on the evidence of the international literature on school interventions for the promotion of the mental health and wellbeing of children and adolescents. It is focused on five topical main areas: promoting general health and wellbeing; programs targeting specific mental disorders and conditions and integration of adolescents with mental health problems; Bullying; Sport; Alcohol and Drugs. An additional paper on the results of the largest epidemiological study conducted in some European countries on the prevalence and relative risk factors of mental disorders in school-age completes the issue. Conclusion: These reviews are a first contribution to address future European research and interventions, in particular about the multiple ways through which European policies could support the schooling and wellbeing of children and adolescents.